Wear behaviour of SiC reinforced 2124 Al alloy composite in RWAT system - Izciler, M; Muratoglu, M (Elsevier Science Sa, 2003)
The low stress wear behaviour of 25 vol.% SiC reinforced 2124 Al alloy composite produced by powder metallurgy method, was investigated in a rubber wheel abrasion test (RWAT) apparatus at different loads. SiC and Al2O3 abrasive particles were used as the abrasive medium. Wear tests were performed under the loads of 30, 60 and 90 N at the room temperature. It has been found that the wear rate of the composites increased with increasing the load. Wear rate of the composites abraded by SiC abrasive particles showed higher value than that of the composites abraded by Al2O3 abrasive particles. (C) 2002 Elsevier Science B.V. All rights reserved.
Keywords: low stress wear behaviour; Al-Cu/SiC composite; RWAT system